Релятивистский магнетронный генератор - Канаев Г. Г. Геннадий Григорьевич; Перелыгин С. Ф.; Сулакшин А. С.; Фоменко Г. П.; Фурман Э. Г. Эдвин Гугович; Штейн Ю. Г.; Юшков Ю. Г. Юрий Георгиевич
опубл. 07.01.81